Pediatric Ankle Syndesmosis Injuries: Current Concept Review - Alexanian, Ara; Loveland, Kerry; Friebele, Jill Christine (Journal of the Pediatric Orthopaedic Society of North America, 2022)
Ankle syndesmosis injuries occur in 1% of pediatric ankle trauma. In the younger populations, an open physis has been thought to be a protective factor against syndesmotic injury and therefore favoring more Salter-Harris type injuries. Clinical methods used to diagnose syndesmotic injuries may not be effective in the pediatric population. Radiographic findings are mostly based on the study of adolescent and adult populations. Therefore, syndesmotic injuries may be overlooked in the younger pediatric patient with ankle trauma and open physes. Here we present a review of the literature of ankle syndesmotic injuries and a case report of such an injury that was initially missed in the younger pediatric patient. Further research is needed to characterize the ankle syndesmosis in the younger pediatric patient, how this may change with time and growth, clinical exam findings that may accurately diagnose a syndesmotic injury, and radiographic findings concerning for syndesmotic injury in this population.